Effect of Pre-sowing Seed Treatments in Hypericum perforatum L: A High Value Medicinal Plant - JITENDRA S. BUTOLA; SHREEKAR PANT; S.S. SAMANT (Seed Research, 2026)
Hypericum perforatum L. is a high value vulnerable medicinal plant of the Indian Himalayan Region. Seeds of this species showed poor germination. In present study, of the total 15 pre-sowing treatments tried, 13 significantly (P < 0.05) stimulated seed-germination, where GA3 (150 μΜ), ΚΝΟ, (150 mM) and NaHCO3 (15 minutes) were found to be most effective. The control showed only 27.8% germination while it increased highest upto 71.1% by KNO3 (150 mM). These treatments were also effective in reducing the time required for germination and mean germination time. In view of the low cost and easy applicability of KNO and NaHCIO, compared to the expensive and technically complicated plant growth regulators, these chemicals could be used by poor and unskilled farmers of the Indian Himalayan Region for the ex-situ cultivation of H. perforatum.